2018
DOI: 10.1245/s10434-018-6656-6
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcome of Definitive Chemoradiotherapy and Induction Chemoradiotherapy Followed by Surgery for T4 Esophageal Cancer with Tracheobronchial Invasion

Abstract: Clinical LN negativity and later treatment period were significantly good prognostic factors for T4 EC with TBI. The recent improvements in dCRT outcomes may help to achieve survival comparable to that of iCRT-S.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…A retrospective study from the National Cancer Database conducted by Cushman et al [4] revealed that traditional risk factors like age, histology, and clinical nodal stage had no significant impact on overall survival in unresectable esophageal cancer. Yamaguchi et al [5] reported only clinical N0 and later treatment period were related to a better prognosis. The paucity of reliable prognostic factors for unresectable esophageal cancer made us seek for a more potent prognosticator.…”
Section: Introductionmentioning
confidence: 97%
“…A retrospective study from the National Cancer Database conducted by Cushman et al [4] revealed that traditional risk factors like age, histology, and clinical nodal stage had no significant impact on overall survival in unresectable esophageal cancer. Yamaguchi et al [5] reported only clinical N0 and later treatment period were related to a better prognosis. The paucity of reliable prognostic factors for unresectable esophageal cancer made us seek for a more potent prognosticator.…”
Section: Introductionmentioning
confidence: 97%
“…However, these results depend largely on completeness of the resection since the median survival of patients who undergo an incomplete resection rarely exceeds the 6 months. [11][12][13] Radical resection rates for salvage esophagectomies used to treat cT4b tumors vary widely, and high perioperative complication rates are observed, emphasizing the complexity of this procedure. 9,[14][15][16][17][18][19] Therefore, strategies to improve these surgical outcomes should be explored.…”
mentioning
confidence: 99%
“…On CT scan, adjacent thoracic aorta was considered to be involved if the tumor was attached to the artery at a contact angle of ⩾90°. 10 , 11 Diagnosis of metastasis to lymph nodes was based on CT, EUS, and ultrasonography findings.…”
Section: Methodsmentioning
confidence: 99%
“…However, it is not clear whether survival is better in patients opting for surgery than in those opting for completing dCRT. 10 , 11 …”
Section: Introductionmentioning
confidence: 99%